Role and impression management of women lawyers in the home and workplace - Cruz, Ana Carmela B.
This study focused on the roles of women in the home and their impression management strategies they do in the workplace. The research objectives were: to analyze the roles of women lawyers in their home and in their workplace, to know the difference of the impressions of women lawyers from their workplace to their families, to understand how the women lawyers balance their roles as mothers and as lawyers, and to differentiate the self-presentation of women lawyers in their family and in their workplace.